Enhancing Mechanic’s Well-Being Through Ergonomic Design: A Qfd-Based Approach To Optimizing Mechanic Creepers - Amir Rafiqin, Mohd Noh (2025)
The need for ergonomic tools in automotive workshops has increased in recent years due to the increasing awareness of work-related musculoskeletal disorders (WMSD) among mechanics. This has encouraged researchers to identify ways to improve the ergonomic design of mechanic creepers. This study focused on improving the design of mechanic creepers to improve user comfort and reduce physical strain. A key challenge in current designs is balancing structural durability with ergonomic support, particularly for the neck and lumbar regions. Existing creepers often lack features to adequately support mechanics' well-being, highlighting the need for designs that address ergonomic deficiencies while maintaining durability and functionality. This study used a cross- sectional field study using simple random sampling to assess the material composition, ergonomic performance, and user satisfaction of mechanic creepers. Data were collected through surveys and observations, with descriptive statistics analyzed using SPSS to identify trends and areas for improvement. The findings revealed significant deficiencies in neck and lumbar support and emphasized the importance of durable components, particularly for the wheels, which are prone to damage. Based on the analysis, recommendations were made to improve the durability of the wheels and combine adjustable features with enhanced padding for better neck and lumbar support. These improvements were made to create better posture and reduce physical strain, improve mechanic well-being and minimize the prevalence of WMSD in the workshop environment. Adopting ergonomic design principles, such as improved padding materials and adjustability, is essential to creating a more user-friendly mechanic crawler that supports worker health and productivity.